(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Using GIS can assist in collecting data and displaying them to provide a complete picture about the state of disease from pandemic to epidemic. The GIS technique can, specially, help to find solutions to stop diseases and determine fast and accurately the populations exposed and expected to be infected by the contagious and endemic diseases. Mapping the disease spreading among the groups exposed to the risks and the services date can help planners determine where they can increase the precautions and medical activities immediately, as it can help in tracking of the outbreak, so that the planners could recognize the infected areas and restrict them. It also can assist in foreseeing a specific pandemic, follow and observe virus movements while spreading, specify the source of diseases and how these diseases vary from a place to another and deal with the emergencies, and, finally, diagnose and control disease vector through developing a database to those areas